The Hyperorder of Solutions of Second-Order Linear Differential Equations - Guowei Zhang (Abstract and Applied Analysis)
We prove that the hyperorder of every nontrivial solution of homogenous linear differential equations of type and nonhomogeneous equation of type is one, where are entire functions of order less than one, improving the previous results of Chen, Wang, and Laine.